Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2147/jir.s218105
|View full text |Cite
|
Sign up to set email alerts
|

<p>Assessment of T helper 17-associated cytokines in thromboangiitis obliterans</p>

Abstract: BackgroundThe management of thromboangiitis obliterans (TAO) remains a medical challenge because of its unknown etiology. It is also not known whether it is a systemic or localized disease or a type of autoimmune vasculitis.MethodsIn this study, we evaluated the serum level of IL-17 and IL-23 which increase in both systemic inflammation and autoimmunity, in 60 TAO patients and 30 age- and smoking habit-matched controls. Also, IL-22, which has reported high level during infection but not in autoimmunity, was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…Notably, according to previous studies regarding the evaluation of IL-17, toll-like receptor 4 (TLR4), neopterin and high sensitivity C-reactive protein (hsCRP) on the same TAO samples, 9,10 there was a significant negative correlation between IL-33 and IL-17 (p = 0.041, CC = −0.42). Also, the IL-33 level was 459 ± 125.5ng/mL in CRP-negative patients and 222.6 ± 11.26ng/mL in CRP-positive patients (p = 0.017, Z = −2.38).…”
Section: Resultsmentioning
confidence: 90%
“…Notably, according to previous studies regarding the evaluation of IL-17, toll-like receptor 4 (TLR4), neopterin and high sensitivity C-reactive protein (hsCRP) on the same TAO samples, 9,10 there was a significant negative correlation between IL-33 and IL-17 (p = 0.041, CC = −0.42). Also, the IL-33 level was 459 ± 125.5ng/mL in CRP-negative patients and 222.6 ± 11.26ng/mL in CRP-positive patients (p = 0.017, Z = −2.38).…”
Section: Resultsmentioning
confidence: 90%
“…Despite the studies on pathophysiology (reviewed in [29,51], actually, the detailed etiopathogenesis and molecular mechanisms are still unknown. Among the possible biomolecular hypotheses [10,12,14,18,[20][21][22][23]27,50,[54][55][56], oxidative stress has been crucially indicated as an important factor for both the initiation and progression of WBD [30,31,51,54].…”
Section: Discussionmentioning
confidence: 99%
“…Among the immunologic and inflammatory biomolecular hypotheses for the WBD disease, some biomarkers and biochemical mechanisms have been identified. Among them, crucial roles are played by cytokines and chemokines [10][11][12], adhesion molecules [13][14][15], Rickettsia rickettsii and Porphyromonas gingivalis (through toll-like receptors) [16][17][18][19], angiogenic factors [20], catecholamines [21], inflammation on sympathetic ganglia [22], T cells/macrophages/dendritic cells (intima infiltration of vessels) [23], accumulation of immunoglobulins, immune complexes and complement factors on sub-endothelial elastic lamina [24], urinary cotinine [25], circulating auto-antibodies [26], heme oxygenase 1 and the inducible isozyme of nitric oxide synthase [27], and matrix metalloproteinases [28] (as reviewed in [29]).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to atherosclerosis or vasculitis, low mean platelet volume (MPV) has been observed in TAO patients [14]. MPV is an indicator of platelet activation, and there is strong evidence indicating that MPV is an important variable and that larger platelets have a higher thrombogenicity.…”
Section: Complete Blood Count (Cbc)mentioning
confidence: 99%
“…MPV is an indicator of platelet activation, and there is strong evidence indicating that MPV is an important variable and that larger platelets have a higher thrombogenicity. It is implicated that the severe inflammatory condition has been associated with low MPV, which increases with anti-inflammatory therapy [14]. Interestingly, it has been reported that other metabolic disorders, such as high cholesterol and diabetes, have an association with increased MPV, and this could indicate a link between increased MPV and atherosclerosis [15].…”
Section: Complete Blood Count (Cbc)mentioning
confidence: 99%